Charlie Davis's in Kathleen Glasgow's Girl in Pieces - Nur Laili Putri; Tri Pramesti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Anxiety disorder is an excessive fear and worry about something bad going on. Anxiety can bring influence in the someone’s character. When a people feel anxious and uncomfortable, they can find ways to overcome their anxiety. This study discusses about the Charlie Davis’s anxiety and the causes and effects of Charlie’s anxiety. The method used is the descriptive qualitative method. Data is collected from every page of the novel which includes every quote or conversation by reading, highlights and repeating with everything related to this thesis. By combining theories by Sigmund Freud, Booree, Nevid, and Narramore, this study aims to gain a more comprehensive understanding of anxiety because they are considered most appropriate for analyzing Charlie Davis' anxiety. After analyzing the novel, the writer finds that there are some anxieties experienced by Charlie Davis such as feelings of confinement and isolation, she has a selective mutism, difficulty breathing, panic attacks, inability to concentrate, hypervigilance, fear of something that happens in the future and avoidance behavior. There are several underlying causes why Charlie Davis develop the anxiety disorder such as her father committed suicide, sexual abuse, child neglect, violence by her mother, bullying, best friend died, homelessness and poverty. The causes of Charlie's anxiety affects her life. The effects are: she reserves herself, blame on her, lost trust in other, self-harm, drug and alcohol misuse. After that, the writer finds out how Charlie Davis overcomes her anxiety. There are several things that help Charlie Davis get better, the first is that Charlie finds a new environment that can understand her pain. Then, Charlie become a creative human being with art therapy. And Charlie makes the decision to move a new place to get a better life in Arizona.